Flower Pollination Algorithm-Based MPPT for PEM Fuel Cells with Interleaved Buck-Boost Converter - Pressa Perdana Surya saputra; Zainal Mustakim; Heri Ardiansyah (Universitas Nurul Jadid, 2026)
This study proposes an enhanced maximum power point tracking (MPPT) system for protons exchange membrane fuel cell (PEMFC) by integrating a Flower Pollination Algorithm (FPA)-based controller with an IBBC (interleaved buck–boost converter). The non-linear behavior of electrochemical properties of PEMFCs pose significant challenges to conventional MPPT techniques, which often struggle to maintain accurate and stable power tracking under varying operating conditions. Many existing approaches rely primarily on properties like as membrane water content, hydrogen pressure and cell temperature to regulate converter operation. Proposed FPA-based MPPT method improves tracking accuracy and dynamic performance in response to changes in content of membrane water and temperature. In addition, interleaved buck–boost topology reduces output current ripple and distributes current stress across switching devices, contributing to enhanced efficiency and system stability. Simulation results demonstrate that the proposed strategy achieve convergence faster to maximum power point, lower steady-state oscillations, and improved power extraction efficiency compared with conventional MPPT methods across diverse PEMFC operating scenarios.